(3JJeI UhGf GdMceIs - (3GdHjgbj XgjQGdOjf CHi GdMSf Ydj Hf CHi GdbGSe RjO GdHjgbjs
(3BNQgG (B:s
(3CKfGA JQLeI GdCejQ GdSjO ESeGYjd GdMSjfi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B75 (3C (B- (3U(B133 (3Hs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B324 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B78 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJGQjNs